2012
DOI: 10.1039/c1sm06672b
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting time–composition equivalence in ternary block copolymer/cosolvent systems

Abstract: Time-temperature rheological equivalence is one of the most important and broadly used concepts developed with regard to the viscoelastic behavior of polymers. In this study, we explore the generality of an analogous relationship, time-composition equivalence, in several series of ternary block copolymer/cosolvent systems at ambient temperature. Of particular interest are triblock copolymers solvated with a miscible mixture of midblock-selective solvents to yield physical gels. Such gels, consisting of a midbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…(In previous studies, 41 the molecular weight characteristics of the copolymer reported by the manufacturer were provided.) For consistency with our previous TPEG studies, 37,42 an aliphatic : alicyclic (70 : 30) mineral oil (Hydrobrite 380) with a molecular weight of $500 Da was obtained from Sonneborn, Inc. and used without further purication. Reagent-grade toluene and hydrochloric (HCl) acid were purchased from Sigma-Aldrich and likewise used as-received.…”
Section: Methodsmentioning
confidence: 99%
“…(In previous studies, 41 the molecular weight characteristics of the copolymer reported by the manufacturer were provided.) For consistency with our previous TPEG studies, 37,42 an aliphatic : alicyclic (70 : 30) mineral oil (Hydrobrite 380) with a molecular weight of $500 Da was obtained from Sonneborn, Inc. and used without further purication. Reagent-grade toluene and hydrochloric (HCl) acid were purchased from Sigma-Aldrich and likewise used as-received.…”
Section: Methodsmentioning
confidence: 99%
“…First, 'tuning' the composition and therefore the viscosity of the solvent of a polymeric system accesses different time scales. 33 For us, since the background sugar solution (70-87% sugar) is close to its glass transition, 21 we expect that viscosity is mainly 'tuned' by the (sugar : water) ratio.…”
Section: The Physical Significance Of Tcsmentioning
confidence: 99%
“…8 In the presence of miscible co-solvents with comparable block selectivity but different viscosities, these materials display evidence of time-composition equivalence. 9,10 For these reasons, they are uniquely suitable for use as shockabsorbing media and energy-efficient electroelastomers. [11][12][13] Conversely, in sulfonated block copolymers, a polar blockselective solvent such as water can be added to swell these materials for potential use as polyelectrolyte membranes (PEMs) 14 or as ionic electroactive polymers.…”
Section: Introductionmentioning
confidence: 99%